Effects of oral sodium supplementation on indices of thermoregulation in trained, endurance athletes - Earhart, E. L.; Weiss, E. P.; Rahman, R.; Kelly, P. V. (Journal of Sports Science & Medicine, 2015)
Guidelines recommend the consumption of sodium during exercise to replace losses in sweat; however, the effects of sodium on thermoregulation are less clear. To determine the effects of high-dose sodium supplementation on indices of thermoregulation and related outcomes, 11 endurance athletes participated in a double-blind, randomized-sequence, crossover study in which they underwent 2-hrs of endurance exercise at 60% heart rate reserve with 1800 mg of sodium supplementation (SS) during one trial and placebo (PL) during the other trial. A progressive intensity time-to-exhaustion test was performed after the 2-hr steady state exercise as an assessment of exercise performance. Sweat rate was calculated from changes in body weight, accounting for fluid intake and urinary losses. Ratings of perceived exertion (RPE) and heat stress were assessed using verbal numeric scales. Cardiovascular drift was determined from the rise in HR during the 2-hr steady state exercise test. Skin temperature was measured with an infrared thermometer. Dehydration occurred in both SS and PL trials, as evidenced by substantial weight loss (2.03 ± 0.43% and 2.27 ± 0.70%, respectively; p = 0.261 between trials). Sweat rate was 1015.53 ± 239.10 ml·hr-1 during the SS trial and 1053.60±278.24 ml/hr during the PL trial, with no difference between trials (p = 0.459). Heat stress ratings indicated moderate heat stress ("warm/hot" ratings) but were not different between trials (p = 0.825). Time to exhaustion during the SS trial was 6.88 ± 3.88 minutes and during the PL trial averaged 6.96 ± 3.61 minutes, but did not differ between trials (p = 0.919). Cardiovascular drift, skin temperature, and RPE did not differ between trials (all p > 0.05). High-dose sodium supplementation does not appear to impact thermoregulation, cardiovascular drift, or physical performance in trained, endurance athletes. However, in light of the possibility that high sodium intakes might have other adverse effects, such as hypertension, it is our recommendation that athletes interpret professional recommendations for sodium needs during exercise with caution.